2016
DOI: 10.1089/dna.2016.3282
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-497 Modulates Breast Cancer Cell Proliferation, Invasion, and Survival by Targeting SMAD7

Abstract: As an inhibitor of TGF-β signaling, SMAD7 was reported to play dual roles in breast cancer development and progression. It inhibited the cancer metastasis by blocking epithelial-mesenchymal transition, however, litter studies focused on its role in other cancer processes. In this study, miR-497 expression was found inversely correlated with SMAD7 expression in breast cancer tissues. Bioinformatics analyses defined a potential miR-497 response element within 3' untranslated region of SMAD7 that was validated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Twelve studies reported adjusted HRs; the models described in these studies included covariates such as age, tumor site, grade, or disease stage (Table 1). In the included articles, increased expression of miR-27a/b, [15,16,18,19] miR-34b, [20] miR-210, [14] miR-125b, [21] miR-655, [21] miR-21, [22,23] miR-18b, [24] miR-103, [24] miR-107, [24] miR-652, [24] miR-301a, [25] miR-30e, [15] miR-214 [26] and miR-454 [17] decreased expression of miR-155, [15,21,27,28] miR-16, [21] miR-374a/b, [19,21] miR-497, [15,29] miR-493, [15] miR-185, [30] miR-26a, [31] miR-126-3p, [19] miR-218-5p [19] and miR-361-5p [32] were associated with poor prognosis in TNBC. Among these miRs, 6 (miR-155, miR-21, miR-27a/b, miR-374a/b, miR-210, and miR-454) were reported by at least 2 studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported adjusted HRs; the models described in these studies included covariates such as age, tumor site, grade, or disease stage (Table 1). In the included articles, increased expression of miR-27a/b, [15,16,18,19] miR-34b, [20] miR-210, [14] miR-125b, [21] miR-655, [21] miR-21, [22,23] miR-18b, [24] miR-103, [24] miR-107, [24] miR-652, [24] miR-301a, [25] miR-30e, [15] miR-214 [26] and miR-454 [17] decreased expression of miR-155, [15,21,27,28] miR-16, [21] miR-374a/b, [19,21] miR-497, [15,29] miR-493, [15] miR-185, [30] miR-26a, [31] miR-126-3p, [19] miR-218-5p [19] and miR-361-5p [32] were associated with poor prognosis in TNBC. Among these miRs, 6 (miR-155, miR-21, miR-27a/b, miR-374a/b, miR-210, and miR-454) were reported by at least 2 studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous studies have revealed that miR-497 is downregulated in breast cancer tissues and cell lines ( 27 29 ). Low expression levels of miR-497 indicate a poorer prognosis for patients with breast cancer ( 30 ). Wang et al ( 31 ) reported that miR-497 expression levels are reduced in colorectal cancer and correlate closely with clinical stage and lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between miRNAs dysregulation and human disease are investigated from variable disease. MiR-497, being one of miR-15 family members, is mainly identified as a tumor suppressor in various cancers, such as hepatocellular carcinoma [5], osteosarcoma [67] and breast cancer [8]. Recently, miR-15 family members were identified as novel regulators in cardiac hypertrophy and fibrosis by inhibition of the TGFβ pathway [9].…”
Section: Introductionmentioning
confidence: 99%